Metode Read Aloud dalam Meningkatkan Kemampuan Bahasa Anak Usia Dini - Hernawati, I; Putriyanti, Lina; Sulianto, Joko (Jurnal Pendidikan Anak Usia Dini, 2026)
This study analyzes the effectiveness of the read-aloud method in enhancing receptive and expressive language skills in early childhood through a qualitative Systematic Literature Review (SLR). Using literature from reputable databases (2010–2025), the study filtered 167 identified articles down to 12 core papers for thematic analysis. Findings indicate that the read-aloud method significantly improves story comprehension, vocabulary expansion, and children's ability to communicate and retell stories. Key success factors include active teacher-child interactions, such as expressive intonation, predictive questioning, and two-way dialogue. Beyond linguistic gains, the method strengthens foundational literacy, increases engagement, and fosters a positive attitude toward books. The study concludes that the read-aloud method is a valid, relevant, and essential strategy for early childhood education (ECE) institutions. Implementing this method routinely and structurally is recommended to optimize language and literacy development in young learners. As a proven pedagogical tool, it bridges the gap between basic communication and advanced literacy readiness.